Electroacupuncture Promotes Proliferation of Amplifying Neural Progenitors and Preserves Quiescent Neural Progenitors from Apoptosis to Alleviate Depressive-Like and Anxiety-Like Behaviours - Yang, Liu (Hindawi Publishing Corporation, 2014)
The present study was designed to investigate the effects of electroacupuncture (EA) on depressive-like and anxiety-like behaviours and neural progenitors in the hippocampal dentate gyrus (DG) in a chronic unpredictable stress (CUS) rat model of depression. After being exposed to a CUS procedure for 2 weeks, rats were subjected to EA treatment, which was performed on acupoints Du-20 (Bai-Hui) and GB-34 (Yang-Ling-Quan), once every other day for 15 consecutive days (including 8 treatments), with each treatment lasting for 30 min. The behavioural tests (i.e., forced swimming test, elevated plus-maze test, and open-field entries test) revealed that EA alleviated the depressive-like and anxiety-like behaviours of the stressed rats. Immunohistochemical results showed that proliferative cells (BrdU-positive) in the EA group were significantly larger in number compared with the Model group. Further, the results showed that EA significantly promoted the proliferation of amplifying neural progenitors (ANPs) and simultaneously inhibited the apoptosis of quiescent neural progenitors (QNPs). In a word, the mechanism underlying the antidepressant-like effects of EA is associated with enhancement of ANPs proliferation and preserving QNPs from apoptosis.